An Interpretation of the Fan Theorem in Type Theory - Fridlender, Daniel (BRICS Report Series, 1998)
This article presents a formulation of the fan theorem in Martin-L¨of’s type theory. Starting from one of the standard versions of the fan theorem we gradually introduce reformulations leading to a final version which is easy to interpret in type theory. Finally we describe a formal proof of that final version of the fan theorem. Keywords: type theory, fan theorem, inductive bar.